Danmarks første nationalordbog. Om Videnskabernes Selskabs Ordbog I-VIII (1793-1905) - Bergenholtz, Henning; Pálfi, Loránd-Levente (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2014)
The Academy of Science and Letters Dictionary is undoubtedly the Danish dictionary that has had the longest (two centuries), most problematic genesis, and the one most characterised by personal intrigues. This contribution is the first ever to offer a reasonably impartial analysis of selected dictionary entries from the work in connection with a highly detailed review of what was decidedly the most complicated affair in the history of Danish lexicography. We make use of the selective historiographical method that critically selects particularly relevant data and reproduces them in a judgmental and evaluative framework, i.e. a temporally immanent yet critical analysis coupled with a desire to learn from history. The King, i.e. in practice Ove Høegh-Guldberg, who, among other things, financed most of the work, had a clear idea of his target group: the dictionary was intended for the people and scientists – for scholars and laymen, quite simply for all Danes and only for Danes. Nevertheless, it turned out to be a dictionary primarily for scholars. The work was criticised even before the publication of the first volume. The most prominent critic was Peter Erasmus Müller, who referred specifically to individual articles and entries. Since then, the specific criticism of the contents has never been reproduced or discussed and attention has solely been given to the fact that the dictionary was criticised, and was and remained criticizable in general. It is known – because everybody says so – that the dictionary is of little value and repeated without verification that it was the occasion of criticism. However, the Academy of Science and Letters Dictionary is far better than its reputation. Our contribution will show that the prevalent evaluation is not correct. This applies in particular when the criticism is not temporally immanent and is not immanent in relation to the dictionary’s anticipated structure.